1997
DOI: 10.1177/109158189701600104
|View full text |Cite
|
Sign up to set email alerts
|

Amended Final Report On the Safety Assessment of Pyrocatechol

Abstract: Pyrocatechol is a phenol used primarily in hair dyes but has one reported use in skin care preparations. When this ingredient was first reviewed it was concluded that Pyrocatechol was safe for use in formulations designed for discontinuous, brief use followed by rinsing from the skin and hair at concentrations of up to 1.0%. This amendment to that report was prepared in order to incorporate the results from several studies, including those reporting immunologic, carcinogenic, and cocarcinogenic effects of Pyro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Pyrocatechin-as the key BA aerobic disintegration intermediateis similar to endogenous catecholamines with inherent potential to raise blood pressure and dilate airways [83][84][85][86].…”
Section: Ba Metabolism By Microorganismsmentioning
confidence: 99%
“…Pyrocatechin-as the key BA aerobic disintegration intermediateis similar to endogenous catecholamines with inherent potential to raise blood pressure and dilate airways [83][84][85][86].…”
Section: Ba Metabolism By Microorganismsmentioning
confidence: 99%
“…Parabens have been classified 24 as generally regarded as safe (GRAS) by the U.S. Food and Drug 25 Administration (FDA, 2013). The Cosmetic Ingredient Review Panel 26 concluded that parabens used in cosmetics, including BP, do not 27 pose a safety risk based on the available data (Andersen, 2008). 28 More recently, evidence of parabens ability to disrupt endocrine 29 systems at high doses has been published.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast to the previous works utilizing materials like PVDF and PVDF-TrFe, in this research, we have employed PVAc, an inexpensive and degradable polymeric material (also referred to as white glue), for synthesizing the nanofibrous membranes. PVAc is a rubbery, thermoplastic synthetic nontoxic , polymer having the formula (C 4 H 6 O 2 ) n , which makes it a promising candidate for usage in sensors targeted for human physiological monitoring applications.…”
Section: Introductionmentioning
confidence: 99%